Can Prudence Be Enhanced?. Issue 5 (5th September 2018) - Eberl, Jason T
Abstract: Some bioethicists have argued that moral bioenhancement, complementing traditional means of enhancing individuals' moral dispositions, is essential if we are to survive as a species. Traditional means of moral enhancement have historically included civil legislation, socially recognized moral exemplars, religious teachings and disciplines, and familial upbringing. I explore the necessity and feasibility of pursuing methods of moral bioenhancement as a complement to such traditional means, grounding my analysis within a virtue-theoretic framework. Specifically, I focus on the essential intellectual virtue for proper moral reasoning, prudence, and whether proposed methods of moral bioenhancement could facilitate the cultivation of this virtue within the psyches of moral agents. I conclude that certain means of bioenhancement may serve to augment the ability to reason prudentially and assist moral agents to align their wills with their higher-order rational desires, though such means require those higher-order desires to already have been formulated independently.